2022
DOI: 10.1111/andr.13323
|View full text |Cite
|
Sign up to set email alerts
|

Which sperm parameter limits could really guide the clinical decision in assisted reproduction?

Abstract: Background The predictive role of sperm motility and morphology was recently detected in a large sample of more than 20000 assisted reproductive technology (ART) fresh cycles. However, the complete ART procedure consisted of both fresh and frozen‐embryos transfers and only a comprehensive evaluation of the entire process could really confirm if these parameters really predict the ART success. The aim of the study was to evaluate which sperm parameter could predict the success of ART. Methods A retrospective, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…These results confirm the potential predictive role of sperm morphology for ICSI outcomes. Furthermore, frozen IVF cycle success appears to be predicted by progressive sperm motility [ 23 ]. However, lately the trend in the use of IVF rather than ICSI has been reversed in favor of the latter, also in the presence of male factors suitable for the former.…”
Section: Levelmentioning
confidence: 99%
“…These results confirm the potential predictive role of sperm morphology for ICSI outcomes. Furthermore, frozen IVF cycle success appears to be predicted by progressive sperm motility [ 23 ]. However, lately the trend in the use of IVF rather than ICSI has been reversed in favor of the latter, also in the presence of male factors suitable for the former.…”
Section: Levelmentioning
confidence: 99%
“…Impaired sperm parameters such as semen volume, sperm concentration, sperm motility, and total sperm count are closely associated with conception and embryo quality [60,61]. A retrospective, real-world study demonstrated that progressive sperm motility was the main ART outcomes predictor for the frozen cycle, which need to be improved for ART success [62]. Recently, a Bayesian network meta-analysis found that EA can effectively improve sperm motility [63].…”
Section: Acupuncture Improves Sperm Parametersmentioning
confidence: 99%